Geriatric Politics and the American Presidential Election - Katz, Stephen; Achenbaum, W. Andrew (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
When Anita Wohlmann and Aagje Swinnen invited me to write a commentary on age and ageism in the upcoming 2024 American presidential election, I was entranced by the idea. As a Canadian, I have watched with fascination the dramas of American elections from the front row of our international border, beginning with the 1960 debates between Democrat John F. Kennedy and Republican Richard M. Nixon, the first on TV. Both were experienced politicians. Kennedy was a senator and Nixon had been Vice President under Dwight Eisenhower for eight years, thus expected to be debate winner and next President. But TV was not kind to him. Kennedy appeared fit, handsome, charismatic, camera friendly, and most importantly, much younger than Nixon, who was awkward, uncomfortable, hesitant, and sweaty (also recovering from a knee injury). Both were in their forties, Nixon only five years older than Kennedy (see Kraus, 1977).